(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2015)
In the aftermath of the independence referendum of September 2014 we decided to conduct research on how people learned and educated themselves informally leading up to the vote. Given the range of information and issues people faced, particularly over the final six months of the process, hearing how people made sense of it all is clearly an area of interest – particularly for academics, community educators and politicians. Through an online survey conducted in December 2014, we asked people a series of questions to ascertain, amongst other things, how and where they gained information, how they interacted with that information and how they utilised social media (if they did so).